Dasar-Dasar Moderasi dalam Epistemologi Pendidikan Islam Perspektif Al-Qur’an - kerwanto, kerwanto (Islamic Religious Education Departement, 2022)
This article explores the basics of moderation excavated from the verses of the Qur'an, which can be used as the epistemology of education in Islam. The critical value of this study is the critique of the epistemology of modern Western education, which ignores metaphysics as an approach and study in epistemology. Through this article, the author wants to make a description of the human ontology and its axiology from the perspective of the Qur'an as an epistemological foundation in education. It is urgent to do this because the basics of educational epistemology cannot be separated from the human perspective on ontology and axiology. Through the analysis of the verses of the Qur'an, it is illustrated that humans are created in moderation. The dimensions inherent in the reality of human ontology- such as exoteric-esoteric, physical-spiritual, physical-metaphysical, individual (private)-social aspects- are given serious attention by the Qur'an and placed in their respective positions. Another interesting discussion in this article is a description of the ethical-axiological values ​​of a moderate Al-Qur'an perspective, such as the influence of morality, family, worship and prayer on the development of human physical and spiritual aspects. Regarding the research approach, this article can be called a thematic interpretation study because the author tries to collect the verses of the Qur'an in a specific theme and then examines the interrelationships between these verses to produce a general concept.